2021
DOI: 10.5812/jjcmb.116396
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Long Non-coding RNA HOTAIR Suppresses Reverses Epithelial-Mesenchymal Transition in AGS Gastric Cancer Cell Line by Downregulation of Fibronectin 1 and Claudin-4

Abstract: Background: Gastric cancer is the second reason for cancer mortality worldwide, with a high capacity for metastasis. Long non-coding RNAs (lncRNAs) are recently described as lengthy transcripts with no open reading frame. The lncRNAs play an important role in critical cellular and molecular pathways, including cell cycle, growth, differentiation, and apoptosis. Therefore, it is not surprising that abnormal expression of lncRNAs may be involved in human cancers. The HOX antisense intergenic RNA (HOTAIR) is a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Similarly, Padua Alves et al demonstrated that the fibronectin expression level was downregulated, while HO-TAIR was silenced in breast cancer (25). Babapour et al de- termined that silencing the long non-coding RNA HOTAIR suppressed EMT in AGS gastric cancer cell line by downregulating fibronectin 1 (26). HOTAIR has also been detected to reduce transcription level of the metastasis-associated genes like fibronectin (27).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Padua Alves et al demonstrated that the fibronectin expression level was downregulated, while HO-TAIR was silenced in breast cancer (25). Babapour et al de- termined that silencing the long non-coding RNA HOTAIR suppressed EMT in AGS gastric cancer cell line by downregulating fibronectin 1 (26). HOTAIR has also been detected to reduce transcription level of the metastasis-associated genes like fibronectin (27).…”
Section: Discussionmentioning
confidence: 99%